2004
DOI: 10.1627/jpi.47.258
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Co Addition on the Surface Structure and the Activity of Mo/Al<sub>2</sub>O<sub>3</sub> Catalyst for the Hydrogenation of Olefins

Abstract: The present study investigated the effects of Co addition on the surface structure and activity of Mo/Al2O3 for the hydrogenation of C6-C10 olefins. CoMo/Al2O3 (Co/Mo atomic ratio: 0.56) had lower activity for the hydrogenation of 1-hexene, 1-octene and 1-decene than Mo/Al2O3, whereas CoMo/Al2O3 had higher activity for the hydrogenation of 2-octene, 2,4,4-trimethyl-2-pentene and cyclohexene. Co/Al2O3 showed no activity for the hydrogenation of 1-octene and 2,4,4-trimethyl-2-pentene. NO uptake measurements over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Many studies have investigated the difference between HDS and HYD active sites and have suggested that HYD active sites have different properties to HDS active sites. 4-7, [14][15][16] Hatanaka et al proposed that CUS can be classified as follows: (i) n-olefin HYD active sites, (ii) isoolefin HYD active sites, and (iii) HDS active sites. 6 Although, they do not mention the difference in the structures among these active sites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have investigated the difference between HDS and HYD active sites and have suggested that HYD active sites have different properties to HDS active sites. 4-7, [14][15][16] Hatanaka et al proposed that CUS can be classified as follows: (i) n-olefin HYD active sites, (ii) isoolefin HYD active sites, and (iii) HDS active sites. 6 Although, they do not mention the difference in the structures among these active sites.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, CUS will be involved in HYD of unsaturated compounds. Many studies have investigated the difference between HDS and HYD active sites and have suggested that HYD active sites have different properties to HDS active sites , . Hatanaka et al proposed that CUS can be classified as follows: (i) n -olefin HYD active sites, (ii) isoolefin HYD active sites, and (iii) HDS active sites.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, we have already found that HDS activities of Co(or Ni)Mo(or W)/A1 2 O 3 are highly improved when some chelating agents are added in impregnating solutions containing Co (or Ni) ions and Mo (or W) ions [17][18][19][20][21]. The role of chelating agents is considered to form stable chelate-Co complex and to control the timing of sulfiding of Co.…”
Section: Introductionmentioning
confidence: 99%
“…The complexes between Co 2 and chelating agents used in this study have higher stabilities than those reported previously. Thermodynamic calculations in our previous study suggested that these complexes survive the drying step 32) . On the other hand, the present XPS analysis indicated the absence of carbonaceous compounds originating from the chelating agents after calcination (not shown here) 21) , suggesting the importance of the drying and calcination steps.…”
Section: Function Of Chelating Agentsmentioning
confidence: 88%